Implementasi Metode Pembelajaran Kooperatif Model Numbered Head Together Pada Perkuliahan Bahasa Arab Komunikasi - wijayanti, wijayanti wijayanti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
In an effort to improve the quality and quality of education in Indonesia there needs to be some renewal in the world of education both in terms of learning methods, media, and material. The process of teaching and learning activities is no longer dominated by teachers or lecturers but rather is student centered. Some studies in learning show that peer teaching is more effective than teaching by the teacher. Teaching systems that provide opportunities for students to cooperate with fellow students in structured tasks are referred to as